Transcendental Paradigm and the Problem of the Adequacy of Mental Reflection - Naghdyan, Rouben (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
The article compares two systems of postulates, 76 which are basic for the two paradigms of the psychology of perception – classical and transcendental. On the example of the analysis of the problem of the adequacy of perception, a fundamental difference in their methodological resources is shown. If the correspondence between the object and its image is true in the classical paradigm, then in the transcendental paradigm, along with the elimination of the concept of the object, the concept of the adequacy of perception loses its meaning.
Keywords: classical rationality, non-classical rationality, transcendental paradigm, adequacy of perception